Practices of Health Care Workers Regarding Viral Hepatitis in Babylon Province, Iraq - Hamza, Ibrahim Mohsen; Ali, Wasen Abdul-Ameer; Dalal F. Al-Akabi (American Journal of Biomedicine and Pharmacy, 2025)
Background: Viral hepatitis is a significant public health issue, affecting millions of people annually. Health care workers represent high risk population for viral hepatitis infection. Objective: This study seeks to assess the level of practice of healthcare workers regarding viral hepatitis. Methodology: A descriptive cross-sectional study was conducted on healthcare providers in the Babylon Governorate. A convenient, non-probability sample of 365 healthcare providers with less than three years of service working in departments of the selected hospitals. The data collection started from the first of October 2024 till the 31 of December 2024. Results: The results of this study indicate that 44.9% of HCWs have a moderate practice score, followed by 30.7% of the participants have a good practice score, and only 24.4% of HCWs have a poor practice score. The results of this study reveal that there is a significant relationship between demographic (such as age groups, and educational level) and overall practice score (P. value <0.05). These results explain that, age (26-30 years), and high education have good assessment scores for practice about viral hepatitis. Conclusion: The study concludes that the highest proportions of healthcare providers have moderate levels of practices about viral hepatitis. The results reveal that older age, higher education, academic nurses, physicians, those who have completed hepatitis B vaccination, and those who have received training in viral hepatitis prevention and management are associated with good practices regarding viral hepatitis with a p < 0.05.